RNA-Seq-Based Transcriptomics Study to Investigate the Genes Governing Nitrogen Use Efficiency in Indian Wheat Cultivars - Kaur, Sarabjit; Shamshad, M.; Jindal, Suruchi; Kaur, Amandeep; Singh, Satinder; sharma, Achla; Kaur, Satinder (Frontiers in Genetics, 2022)
High NUE (nitrogen use efficiency) has great practical significance for sustainable crop production. Wheat is one of main cultivated crop worldwide for human food and nutrition. However, wheat grain productivity is dependent upon cultivars with high NUE in addition to the application of nitrogen fertilizers. In order to understand the molecular mechanisms exhibiting high NUE response, a comparative transcriptomic study was carried out through RNA-seq analysis to investigate the gene expression that regulate NUE, in root and shoot tissue of N-efficient (PBW677) and N-inefficient (703) cultivar under optimum and nitrogen (N) stress. Differentially expressed genes (DEGs) analysis revealed a total of 2,406 differentially expressed genes (DEGs) present in both the contrasting cultivars under N stress. The efficient genotype PBW677 had considerably more abundant DEGs as 1653 (903root+750shoot) as compared to inefficient cultivar PBW703 as 753 (96root+657shoot). Gene ontology enrichment and pathway analysis of these DEGs suggested that the two cultivars differed in terms of adaptive mechanism. Gene enrichment analysis revealed that among the upregulated and downregulated genes the overrepresented and underrepresented gene categories belonged to the biological processes like DNA binding, response to abiotic stimulus, photosynthesis, carbon fixation, carbohydrate metabolic process, nitrogen compound metabolic process, nitrate transport and translation in cultivar PBW677 while the enriched biological processes were nucleosome assembly, chromatin remodeling, DNA packaging, lipid transport, sulphur compound metabolic process, protein modifications, protein folding and refolding in N inefficient cultivar PBW703. We found several transcription factors (MYB, WRKY, RING finger protein, Zinc finger protein, transporters (NRT1, amino acid transporters, sugar), protein kinases, genes involved in N absorption, transportation and assimilation to be highly expressing in high NUE cultivar PBW677. In our study we report 13 potential candidate genes which were showing alternate gene expression in two contrasting cultivars under study. These genes could serve as potential targets for future breeding programs.